Intelligent data processing : 11th International Conference, IDP 2016, Barcelona, Spain, October 10-14, 2016, Revised selected papers /: 11th International Conference, IDP 2016, Barcelona, Spain, October 10-14, 2016, Revised selected papers. (2019) - Unknown
No abstract available